The Impact of Policy on Farmer Suicide in India: A Scoping Review - Edeh, Jude; Scheyett, Anna (Discoveries in Agriculture and Food Sciences, 2025)
High suicide rates are reported among farmers in India; 400,000 died by suicide between 1995 and 2018. This has resulted in governmental policy-level interventions, however, their effectiveness is unclear. This study explores existing research on policies’ impacts on farmer suicide in India. Using scoping review, we searched literature from 2000 through 2023 for empirically-based articles on policy and farmer suicide in India. We found 17 articles, five of which examined the impact of governmental policies and 12 that examined the impact of policy-modifiable factors on farmer suicide. Policy providing farmers with credit and government spending on flood control and agricultural infrastructure were associated with lower farmer suicide. Most frequently identified policy-modifiable factors were debt, poverty, water and irrigation, small farm size, low wages, cash crops, and illiteracy. While many policies have been established to address farmer suicide in India little research exists to demonstrate their effectiveness. Additional research is needed.